Why the Bible Cannot and Should Not Be Taken Literally - Firestone, Randall S. (Scientific Research, 2014)
This paper argues that there are at least five reasons why the claim that the Bible is to be taken literally defies logic or otherwise makes no sense, and why literalists are in no position to claim that they have the only correct view of biblical teachings. First, many words are imprecise and therefore require interpretation, especially to fill in gaps between general words and their application to specific situations. Second, if you are reading an English version of the Bible you are already dealing with the interpretations of the translator since the earliest Bibles were written in other languages. Third, biblical rules have exceptions, and those exceptions are often not explicitly set forth. Fourth, many of the Bible’s stories defy logic and our experiences of the world. Fifth, there are sometimes two contrary versions of the same event, so if we take one literally then we cannot take the second one literally. In each of these five cases, there is no literal reading to be found. Furthermore, this paper sets forth three additional reasons why such a literalist claim probably should not be made even if it did not defy logic to make such a claim. These include The Scientific Argument: the Bible contradicts modern science; The Historical Argument: the Bible is historically inaccurate; and The Moral Argument: the Bible violates contemporary moral standards.
Keywords: Bible; Literal; Cannot Take Bible Literally; Bible Literality; Bible Literalism; Religion; Philosophy of Language; Philosophy of Religion